IMPROVING EFFICIENCY OF RADIO MAINTENANCE TO ENSURE SAFETY - V. E. Emelyanov; I. A. Polotnyanschicov (Научный вестник МГТУ ГА)
This paper considers the possibility of organizing groups of non-traditional security operation and maintenance of radio systems (RTS) while minimizing the associated operational costs. The Algorithm of solving the task of optimal control is given.